Phase diagram of the three states Potts model with next nearest neighbour interactions on the Bethe lattice - Ganikhodjaev, Nasir; Mukhamedov, Farrukh; Pah, Chin Hee (Elsevier, 2008)
We have found an exact phase diagram of the Potts model with competing nearest neighbor and next nearest neighbor interactions on the Bethe lattice of order two. The diagram consists of five phases: ferromagnetic, paramagnetic, modulated, antiphase and paramodulated, all meeting at the multicritical point (T=0, p=1/3). We report on a new phase which we denote as paramodulated, found at low temperatures and characterized by zero average magnetization lying inside the modulated phase. Such a phase, inherent in the Potts model has no analogues in the Ising setting.